1988
DOI: 10.1007/bf01658061
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the gastric cardia: Surgical management and long‐term survival

Abstract: From 1964 to 1985. a total of 114 patients (94 men and 20 women) were operated on. The resectability rate was 71%, and 53% of the patients were thought potentially curable. Either abdominal or combined abdominal and thoracic approaches were preferred. Proximal esophagogastrectomy (54 casesJ was performed in cases with wide esophageai extension and total gastrectomy (27 cases} was performed for tumors localized in the gastric cardia. There was intraoperative examination of the esophageai margin. There was lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 28 publications
3
12
1
1
Order By: Relevance
“…Although curative resection for gastric cancer is most effective, most cases are in stage III and IV on identification in China [11][12][13] , as seen from the high rate of 74.9% in this study, and many of them were ineligible for radical treatment. Ekbom et al [14] reported that BPP in advanced cases only resulted in the average survival period of 5.9 mo, and none of the patients survived for more than one year, similar to the results of without tumor resection [15] . The average survival periods of patients without operation, with EL and BPP in China, as reported by National Gastric Cancer Cooperation Organization, were 4.1, 4.7, and 5.5 mo, respectively [11] , comparable with our findings (4.6, 5.2, and 6.4 mo, respectively, P>0.05).…”
Section: Discussionmentioning
confidence: 59%
“…Although curative resection for gastric cancer is most effective, most cases are in stage III and IV on identification in China [11][12][13] , as seen from the high rate of 74.9% in this study, and many of them were ineligible for radical treatment. Ekbom et al [14] reported that BPP in advanced cases only resulted in the average survival period of 5.9 mo, and none of the patients survived for more than one year, similar to the results of without tumor resection [15] . The average survival periods of patients without operation, with EL and BPP in China, as reported by National Gastric Cancer Cooperation Organization, were 4.1, 4.7, and 5.5 mo, respectively [11] , comparable with our findings (4.6, 5.2, and 6.4 mo, respectively, P>0.05).…”
Section: Discussionmentioning
confidence: 59%
“…Cancers of the proximal stomach are more likely to have lymph node metastases, present with an advanced stage of disease, and are less amendable to curative resection compared to distal gastric cancers [18]. Despite its increasing incidence worldwide, a consensus on the standard surgical treatment of proximal gastric cancer remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated therapeutic value corresponds to the percentage of patients who will benefit from dissection of each lymph node station MST mean survival time favor of total gastrectomy [13]. Others pointed out there were no differences in the 5-year survival rate as well as in operative mortality between total gastrectomy versus proximal gastrectomy for advanced (pT2-pT4) type II and III carcinoma [6,[27][28][29][30]. Of note, it has never been clarified whether proximal gastrectomy can really provide some benefits, such as a better postoperative quality of life, when compared with total gastrectomy in patients with carcinoma of the cardia.…”
Section: Discussionmentioning
confidence: 99%